Clinical and Biological Importance of Micro RNA in the Formation of Women Reproductive Losses - Kamola A. Sattarova1, Farida M. Ayupova2, Dilnoza D. Saidjalalova3, Dildora A. Ayupova4, Irina S. Ak (Institute of Medico-legal Publications Pvt Ltd, 2020)
Habitual miscarriage is currently one of the most frequent complications of the gestational process, whichis diagnosed in 10-25% of pregnant women. (IuA, 2017) Habitual abortion (miscarriage) - spontaneousinterruption of pregnancy two or more times in a row.So, high expression of miR133a may mediate a decrease in HLA-G expression at the protein level andmay be implicated in the pathogenesis of habitual miscarriage, since HLA-G provides immune tolerance inpregnancy49. So, the literature data suggest that microRNA dysregulation may be related to the pathogenesisof various obstetric complications, but accurate methodological approaches to the diagnosis and predictionof pregnancy complications using microRNA require further study.